Financial statement analysis - Subramanyam, K.R. (New York, NY : McGraw Hill Education, 2014)
The ability to understand and analyze financial statements is important to effective decision making by investors, creditors, analysts, consultants and managers. Financial Statement Analysis equips students with the necessary skills to succeed in the increasingly competitive business environment
Chapter 1: Overview of Financial Statement Analysis -- Chapter 2: Financial Reporting and Analysis -- Chapter 3: Analyzing Financing Activities -- Chapter 4: Analyzing Investing Activities -- Chapter 5: Analyzing Investing Activities: Intercorporate Investments -- Chapter 6: Analyzing Operating Activities -- Chapter 7: Cash Flow Analysis -- Chapter 8: Return on Invested Capital and Profitability Analysis -- Chapter 9: Prospective Analysis -- Chapter 10: Credit Analysis -- Chapter 11: Equity Analysis and Valuation
Includes bibliographical references.
Keywords: FINANCE AND ACCOUNTING